The role of the St. Anna Trough in atlantic water transport into the arctic ocean: a novel radiogenic isotope assessment using iodine, uranium, and neodymium - Pérez-Tribouillier, Habacuc; Jaccard, Samuel; Blaser, Patrick; Christl, Marcus; Creac'h, Layla; Hölemann, Jens A.; Scheiwiller, Marcel; Vockenhuber, Christof; Wefing, Anne-Marie; Casacuberta Arola, Núria (Journal of geophysical research. Oceans, 2025)
The St. Anna Trough (SAT) plays a critical role in Arctic Ocean circulation by facilitating heat and water mass exchange, influencing sea-ice melt and thermohaline dynamics. However, ocean circulation in this key region remains understudied compared to other parts of the Arctic. To better understand water mass pathways, origins, and mixing processes in the SAT, this study analyzes anthropogenic radionuclides iodine-129 (129I) and uranium-236 (236U), alongside neodymium isotopes (εNd). Seawater samples were primarily collected from the SAT and Kara Sea during the 2021 Arctic Century Expedition, with complementary data sets from independent sampling campaigns in the Fram Strait (2021) and Barents Sea (2018) providing broader regional context. Distinct 129I signatures reveal the mixing of Atlantic Waters with Arctic shelf-formed waters, contributing to the formation of Cold Deep Water, which integrates into the intermediate and deep Arctic Ocean. Elevated 236U concentrations in mid-depth samples indicate the intrusion of Arctic-Atlantic Waters into the SAT, underscoring the region's role in Arctic water recirculation and mixing complexity. The εNd data indicate a strong riverine signal from the Ob and Yenisei rivers in the southern Kara Sea and Voronin Trough, whereas SAT surface waters show greater influence from Barents Sea Atlantic Waters. Elevated surface radionuclide concentrations above the Voronin Trough highlight this area as a primary gateway for radionuclides entering the central Arctic. These findings provide new insights into Arctic Ocean circulation and demonstrate the complementary strengths of radionuclides and εNd in resolving water mass transformations and pathways.
Online veröffentlicht: 25. April 2025
Gesehen am 25.11.2025